UET.SIR: An e-Government Information Security Incident Management Support Solution - Hải, Lê Hồng; Hóa, Nguyễn Ngọc; Ổn, Phùng Văn; Đức, Tống Minh; Huy, Ngô Quang (Journal of Science and Technology on Information security, 2023)
Abstract— This paper presents the results of research on building solutions to support information security incident handling in organizations. The proposed solution includes both the procedure for information security incident handling, and the UET.SIR system for supporting information security handling. The process is built on a combination of national and international standards, but is customized to suit e-government practices. The UET.SIR system includes a dedicated USB for collecting digital evidence of ATTT incidents and central software with evidence analysis functions to detect the cause and provide support incident handling. The test results of the UET.SIR system at the Ministry of Natural Resources and Environment have initially demonstrated its practical applicability and support for information security incident handling.